2003
DOI: 10.1081/fst-120025855
|View full text |Cite
|
Sign up to set email alerts
|

Terrestrial and Extraterrestrial Fullerenes

Abstract: This paper reviews reports of occurrences of fullerenes in circumstellar media, interstellar media, meteorites, interplanetary dust particles (IDPs), lunar rocks, hard terrestrial rocks from Shunga (Russia), Sudbury (Canada) and Mitov (Czech Republic), coal, terrestrial sediments from the Cretaceous-Tertiary-Boundary and Permian-Triassic-Boundary, fulgurite, ink sticks, dinosaur eggs, and a tree char. The occurrences are discussed in the context of known and postulated processes of fullerene formation, includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(13 citation statements)
references
References 125 publications
0
13
0
Order By: Relevance
“…Source data of bituminous coal and lignite coal, oil and diesel, gymnosperms, and K/Pg samples are from Li et al (1999), Simoneit (2000, 2001), and Belcher et al (2009), respectively. concentration of fullerenes in the remaining soot will be very small (Kratschmer, 2006). Fullerenes have been extracted from wood charcoal and served as evidence for wildfires (Heymann et al, 1994;Shibuya et al, 1999;Chijiwa et al, 1999;Heymann et al, 2003;Li et al, 2005). There are several reports associated with the detection of fullerenes in the Meishan P/Tr sediments Li et al, 2005;Shen et al, 2006).…”
Section: Other Possible Wildfire Records In the Meishan Sectionmentioning
confidence: 97%
“…Source data of bituminous coal and lignite coal, oil and diesel, gymnosperms, and K/Pg samples are from Li et al (1999), Simoneit (2000, 2001), and Belcher et al (2009), respectively. concentration of fullerenes in the remaining soot will be very small (Kratschmer, 2006). Fullerenes have been extracted from wood charcoal and served as evidence for wildfires (Heymann et al, 1994;Shibuya et al, 1999;Chijiwa et al, 1999;Heymann et al, 2003;Li et al, 2005). There are several reports associated with the detection of fullerenes in the Meishan P/Tr sediments Li et al, 2005;Shen et al, 2006).…”
Section: Other Possible Wildfire Records In the Meishan Sectionmentioning
confidence: 97%
“…Finding anatase within the fulgurite specimen provides further evidence to suggest that the temperature of the glass formation was lower in some regions within the sample than the reported 1800 • C attained, when lightning hits the surface of sand or a rock (Uman 1964;Krider & Dawson 1968). Daly et al (1993) previously reported fullerenes in a fulgurite, though the pathway of fullerenes production could not be definitively linked to the fulgurite formation process (Heymann et al 2003). Graphite has also been observed in fulgurite glasses, presumably resulting from the reduction of organic compounds in the precursor soil (Essene & Fisher 1986).…”
Section: Resultsmentioning
confidence: 97%
“…Solid state formation of fullerenes from an organic precursor, as suggested by Heymann et al (2003) for fullerenes in Shunga, MÌtov and perhaps Sudbury, could be probably ruled out in the case of the Ries crater. This hypothesis demands a possible biogenic precursor and thermal alteration maybe with the presence of elemental sulfur.…”
Section: Discussionmentioning
confidence: 99%
“…The reports on naturally occurring fullerenes have been summarized by Buseck (2002) and by Heymann et al (2003). Fullerenes have been reported in rocks that experienced unique geological events under high-energy conditions, such as lightning (Daly et al 1993), meteorite impacts in Chicxulub, Mexico, at the Cretaceous-Tertiary (K-T) boundary (Heymann et al 1994(Heymann et al , 1998, at the PermianTriassic boundary (Becker et al 2001), and at Sudbury, Canada (Becker et al 1994a, Mossman et al 2003.…”
Section: Introductionmentioning
confidence: 99%